Veterinary drugs : (Ashgate, 2002)
This reference will be an invaluable companion for animal and livestock veterinarians, pharmaceutical researchers, government food and drug regulators, food safety and public health specialists and biologists who, starting with a single synonym or trade name for a veterinary agent, will be able to quickly find a thumbnail sketch of essential information.